SWOT Analysis in the Determination of Competing Strategies (Study at PT. Bank Syariah Indonesia Curup Branch) - Istan, Muhammad (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This research aims to find out and analyze how SWOT analysis in the determination of competing strategies. This research was conducted at PT. BSI Curup Branch Office. The results of this study are internal factors in determining competing strategies in PT. BSI Curup Branch Office consists of strengths including: Good governance and behavior or culture of Sharia Bank, positive investment climate and high work spirit, normal FDR, positive contribution to society and sustainability environment, helping entrepreneurs in Rejang Lebong Regency. And disadvantages include: Limited experts, lack of supporting facilities, lack of supporting rules, promotion or door to door recognition and limited technology. External factors in determining competing strategies in PT. BSI Curup Branch Office consists of opportunities including: Majority of Muslim communities, cooperation, high community potential, MUI fatwa and the opening of KC Pembantu. And the threats include: Total banking share, lack of understanding of Islamic banking, difficult and complicated impressions on Islamic banks, social impressions on Islamic banks and less support from the public. Strategies that can be used one of them to determine competing strategies on PT. BSI Curup Branch Office is a stable growth strategy, meaning in competition in Islamic banking PT. BSI Curup Branch Office.